Wiederholung und Variation im Gespräch des Mittelalters und der Frühen Neuzeit - Roßbach, Nikola; Schrott, Angela (Historische Dialogforschung, 2023)
Repetition is a fundamental cultural act that appears in all fields of human behavior and communication. This volume inquires into the creativity of repetitive conversational patterns in premodernity (German, Spanish, French, English text witnesses).